Hepatitis B virus-like particles expressing Plasmodium falciparum epitopes induce complement-fixing antibodies against the circumsporozoite protein. Issue 12 (14th March 2019) - Kingston, Natalie J.; Kurtovic, Liriye; Walsh, Renae; Joe, Carina; Lovrecz, George; Locarnini, Stephen; Beeson, James G.; Netter, Hans J.
Abstract: The repetitive structure of compact virus-like particles (VLPs) provides high density displays of antigenic sequences, which trigger key parts of the immune system. The hepatitis B virus (HBV) and human papilloma virus (HPV) vaccines exploit the assembly competence of structural proteins, which are the effective immunogenic components of the prophylactic HBV and HPV vaccines, respectively. To optimize vaccine designs and to promote immune responses against protective epitopes, the "Asp-Ala-Asp-Pro" (NANP)-repeat from the Plasmodium falciparum circumsporozoite protein (CSP) was expressed within the exposed, main antigenic site of the small HBV envelope protein (HBsAgS); this differs from the RTS, S vaccine, in which CSP epitopes are fused to the N-terminus of HBsAgS. The chimeric HBsAgS proteins are assembly competent, produce VLPs, and provide a high antigenic density of the NANP repeat sequence. Chimeric VLPs with four or nine NANP-repeats (NANP4 and NANP9, respectively) were expressed in mammalian cells, the HBsAgS- and CSP-specific antigenicity of the VLPs was determined, and the immunogenicity of the VLPs assessed in relation to the induction of anti-HBsAgS and anti-CSP antibody responses. The chimeric VLPs induced high anti-CSP titres in BALB/c mice independent of the number of the NANP repeats. However, the number of NANP repeats influenced the activity of vaccine-induced antibodies measured by complement fixation to CSP, one of the proposed effector mechanisms for Plasmodium neutralization in vivo . Sera from mice immunized with VLPs containing nine NANP repeats performed better in the complement fixation assay than the group with four NANP repeats. The effect of the epitope-specific density on the antibody quality may instruct VLP platform designs to optimize immunological outcomes and vaccine efficacy.